PWE-029 Objective assessment of physical activity as a measure of functional recovery and quality of life following oesophago-gastric cancer resection. (28th May 2012) - Skipworth, R J E; Hendry, P; Paterson-Brown, S; Fearon, K C
Abstract : Introduction: Functional recovery following surgery is determined by the interaction between pre-operative performance, post-operative catabolism, nutritional status, and mood. Physical activity (PA) is an important domain of health-related quality-of-life (HRQL), and may be a useful objective index of recovery. We aimed to use an accelerometer-based activity metre (ActivPAL) to monitor post-operative PA in oesophago-gastric (OG) cancer patients undergoing surgery with curative intent. Methods: PA measures, including step count, time spent in various body positions, and energy expenditure of activity, were assessed over 7-day periods in patients undergoing oesophagectomy or gastrectomy (n=16). Nutritional status, HRQL (FAACT, FACIT-F and EORTC-QLQC30 questionnaires), and mood (HADS questionnaire) were also assessed. Time-points were pre-operatively and 1–2 weeks, 5–6 weeks, 3 months and 6 months post-operatively. Results: Compared with pre-operative results, PA measures were decreased by 23–89% (p<0.05) 1–2 weeks post-operatively, and were still decreased by 15–57% (p<0.05) 5–6 weeks post-operatively. At 3 months, all PA measures except time spent upright (p=0.009) and time spent standing (p=0.013) had recovered. Measures of PA correlated positively with physical and functional domains of HRQL, including EORTC-QLQ30 Global Health Status, FAACT Trial Outcome Index (TOI) and FACIT-TOI (p<0.001), and inversely with HADS-Depression (p<0.001). Conclusion: There is marked impairment of PA at the time of hospital discharge and a gradual recovery over 3–6 months. This carries significant implications in a disease where surgical patients may survive <2 years. PA measures are suitable outcomes for evaluating the impact of enhanced recovery programmes on functional recovery and HRQL. Competing interests: None declared.